Materials for Chemical Sensing - Cesar Paixão, Thiago Regis Longo; Reddy, Subrayal Medapati; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book covers new materials used as analytical devices for increasing the interactions between the development of new analytical devices and materials science. The authors describe how different types of materials such as polymers, self-assembled layers, phthalocyanines, and nanomaterials can further enhance sensitivity and promote selectivity between analytes for different applications. They explain how continuing research and discussion into materials science for chemical sensing is stimulating the search for different strategies and technologies that extract information for these chemical sensors in order to obtain a chemical fingerprint of samples.
Introduction of Materials Used in Chemical Sensors -- Information Extraction Techniques in Chemical Sensing -- (Bio)Chemical Sensors Based on Paper -- Membrane Technologies for Sensing and Biosensing -- Interfacing Graphene for Electrochemical Biosensing -- Nanomaterials as Implantable Sensors -- Self-assembly Thin Films for Sensing -- Phthalocyanines as Sensitive Materials for Chemical Sensors -- Materials for Electronic Tongues: Smart Sensor Combining Different Materials and Chemometric Tools.
Keywords: Materials -- Analysis; Analytical chemistry; Microtechnology; Microelectromechanical systems; Characterization and Analytical Technique; Analytical Chemistry; Microsystems and MEMS